1993
DOI: 10.1111/j.1471-4159.1993.tb05861.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Human Dopamine β‐Hydroxylase Promoter: Transcriptional Induction by Cyclic AMP

Abstract: We have analyzed some functional aspects of the promoter of the human dopamine beta-hydroxylase (DBH) gene. A fragment of 1,247 bp directly 5' to the transcriptional start was progressively shortened, placed in front of a reporter gene, and tested in a human neuroblastoma cell line expressing DBH (SK-N-SH-TFM) and in a monkey kidney cell line (CV-1). A remarkably short region (267 bp), directly upstream from the transcription start, was sufficient to confer activity and tissue-specific expression. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

1994
1994
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 18 publications
0
31
0
Order By: Relevance
“…CRE motifs are of major importance for transcriptional regulation and cAMP induction of several other neuronally expressed genes including somatostatin (Montminy et al, 1986;Andrisani et al, 1987;Powers et al, 1989;Leonard et al, 1992), vasoactive intestinal peptide (Tsukada et al, 1987, Fink et al, 1988Fink et al, 1991), proenkephalin (Comb et al, 1986(Comb et al, , 1988, and dopamine ␤-hydroxylase (Ishiguro et al, 1993;Lamouroux et al, 1993;Kim et al, 1994). Transcriptional control of these genes involves the binding of transcription factors to the CRE motif (for reviews see Goodman (1990), Habener et al (1990), Meyer and Habener (1993), and Lee and Mason (1993)).…”
Section: Discussionmentioning
confidence: 99%
“…CRE motifs are of major importance for transcriptional regulation and cAMP induction of several other neuronally expressed genes including somatostatin (Montminy et al, 1986;Andrisani et al, 1987;Powers et al, 1989;Leonard et al, 1992), vasoactive intestinal peptide (Tsukada et al, 1987, Fink et al, 1988Fink et al, 1991), proenkephalin (Comb et al, 1986(Comb et al, , 1988, and dopamine ␤-hydroxylase (Ishiguro et al, 1993;Lamouroux et al, 1993;Kim et al, 1994). Transcriptional control of these genes involves the binding of transcription factors to the CRE motif (for reviews see Goodman (1990), Habener et al (1990), Meyer and Habener (1993), and Lee and Mason (1993)).…”
Section: Discussionmentioning
confidence: 99%
“…Among several genes specifically expressed in noradrenergic neurons, dopamine ␤-hydroxylase (DBH; EC 1.14.17.1) is a hallmark protein, because noradrenaline is synthesized by this enzyme (Kirshner and Goodall, 1957;Friedman and Kaufman, 1965). Regulation of the DBH gene provides a challenging system for studying neuron-specific gene regulation in general, as well as cell type-specific gene expression in the brain, for the following reasons: (1) DBH is expressed restrictively in noradrenergic and adrenergic neurons and neurosecretary cells in the nervous system; (2) differential expression of DBH among catecholaminergic neurons underlies phenotypic subspecifications among catecholaminergic neurons; that is, whereas tyrosine hydroxylase (TH) is expressed both in dopaminergic and noradrenergic neurons, DBH is expressed only in noradrenergic neurons; and (3) expression of DBH is modulated in response to a variety of trans-synaptic signals, hormones, growth factors, and stress (Otten and Thoenen, 1976;Sabban et al, 1983;Acheson et al, 1984;Faucon Biguet et al, 1986;Lewis et al, 1987;Badoyannis et al, 1991;McMahon et al, 1992; K. T. Lamouroux et al, 1993;Wessel and Joh, 1993).…”
Section: Abstract: Dopamine ␤-Hydroxylase; Transcriptional Regulatiomentioning
confidence: 99%
“…Cell culture studies using transient expression analyses have demonstrated that the upstream sequences of the DBH gene can drive expression of the reporter gene in a cell-specific manner (Shaskus et al, 1992(Shaskus et al, , 1995Ishiguro et al, 1993Ishiguro et al, , 1995Lamouroux et al, 1993). Upstream sequences of the human and rat DBH genes as short as 486 and 395 bp, respectively, direct cell-specific expression, suggesting that these 5Ј-promoter areas may contain important genetic elements for DBH gene regulation (Shaskus et al, 1992;Ishiguro et al, 1993).…”
Section: Abstract: Dopamine ␤-Hydroxylase; Transcriptional Regulatiomentioning
confidence: 99%
See 1 more Smart Citation
“…The factors involved in the regulation of DBH expression are not yet completely characterized. The 5' flanking region of the DBH gene contains several putative positive and negative regulatory elements, including silencer, putative glucocorticoid regulatory element(s), AP-2-like site, and a composite region (DB I) containing adjacent and overlapping cis-regulatory elements found to be involved in basal and second messengerinducible transcription (Kobayashi eta!., 1989;McMahon and Sabban, 1992;Shaskus et al, 1992;Ishiguro eta!., 1993;Lamouroux et al, 1993;Hoyle et al, 1994;Greco et al, 1995;Afar et al, 1996;Seo et al, 1996). It encompasses a sequence similar to both the consensus AP-1 and cyclic AMPresponse~Iements.…”
Section: Essential Role Of C-fos In the Regulation Of Dbh Mrna Levelsmentioning
confidence: 99%